PERANCANGAN SISTEM KENDALI MANUVER OTOMATIS BERBASIS LOGIKA FUZZY PADA PC-40 GUNA MENGATASI HUMAN ERROR - Patih Riau Agung Purba; Emil Syam; Umi Salamah (AKADEMI ANGKATAN LAUT, 2021)
Warships of the Republic of Indonesia (KRI) have the task of securing the waters ofthe Republic of Indonesia from disturbances and threats from outside and within thecountry. The application of current technology allows the KRI to be able to carry outits main tasks. The design of an automatic maneuver control system based on fuzzylogic by utilizing the Global Positioning System (GPS) as a ship positioning module. Allship trajectory data input will be entered into the system and will be processed by theESP8266 microcontroller module. This fuzzy logic is taken to overcome disturbancesthat occur during the voyage which can disrupt the stability and position in the ship,so that when experiencing disturbances the ship will remain in a stable condition andposition the specified shipping trajectory. This system is designed using the programminglanguage in the Arduino IDE application and has been tested. From the results of thisstudy, it was found that the working mechanism of the system starts when the ship ison a voyage by entering the target point in the form of GPS coordinates, the system willcalculate the distance automatically and the GPS sensor will provide data on the ship’sposition, when the ship experiences disturbance, the gyro sensor will give a signal. thenthe system produces output in the form of a rudder change command. This automaticmaneuvering system can overcome human error and has an error tolerance of ± 2.46m. A further development, a data logger data collection system can be added so thatit can be used as a reference when a failure occurs, and before being implementedfurther research is carried out by the Indonesian Navy Research and DevelopmentService.